Integrating Customary Criminal Sanctions in The Resolution of Domestic Violence in Maluku - Latupeirissa, Julianus Edwin; Salamor, Anna Maria (DiH: Jurnal Ilmu Hukum, 2025)
This study aims to examine the existence of customary criminal sanctions in resolving domestic violence (DV) cases in Maluku, particularly in the West Seram Regency. The research employs an empirical approach with a socio-legal model, combining the analysis of primary field data with a review of relevant legal literature. The high prevalence of domestic violence in Maluku, which continues to rise annually, raises significant concerns within society. This phenomenon not only affects victims physically and psychologically but also exacerbates social stigma against women and children who experience violence. Patriarchal culture in Indonesia reinforces gender inequality, where men are often viewed as dominant, normalizing violence against women in some instances. Additionally, victims' economic dependence on perpetrators further aggravates their situations. In Maluku, customary law plays a crucial role in community life, including in addressing domestic conflicts. However, the dominance of national criminal law, introduced during the colonial era, has marginalized the role of customary law. Despite this, in certain areas, such as West Seram Regency, customary criminal sanctions continue to be utilized for resolving domestic violence cases. The findings reveal that some customary communities in Maluku still practice traditional mechanisms to resolve DV cases. These mechanisms involve imposing customary sanctions, such as property compensation or community labor, aimed at restoring social and cosmic balance. While these practices are widely accepted within customary communities, they have limitations in addressing justice and trauma recovery for victims. The approach often emphasizes material resolutions without adequately addressing the psychological and social rehabilitation of victims.